Kepemerintahan Bencana (Disaster Governance) Asia Tenggara - Mohammad Syaban (Department of International Relations, Universitas Andalas)
This research describes the model of disaster governance in Southeast Asia through the Association of South East Asia Nations (ASEAN) framework as the regional organization. Through ASEAN Agreement on Disaster Management and Emergency Response (AADMER) and supported by ASEAN Social Culture and Political Security Community approaches AADMER involves inter-sectors actors (ASEAN, Dialogue Partner Countries and Civil Society Organizations) as the specific effort in order to support regional disaster management cooperation. South East Asia as the vulnerable region has strategic and integrated regional policies as the effort to minimize disaster risk factors. This research is using descriptive-analytical approach as the tool of analysis and supported with secondary data for the methological approaches. The focus of this research is to discovering a model of disaster governance in Southeast Asia region through collaboration from ASEAN, Dialogue Partner Countries (represented by ASEAN Regional Forum Cooperation and ASEAN Defense Minister Meeting Plus) and Civil Society Organization. ASEAN has been developed disaster governance by the utilization of AADMER as the policy foundation, maximize the involvement of non-state actor completed with extensive network through involved civil and military cooperation which demonstrate pluracentric rather than unicentric approach and governing without government process describe the model of disaster management cooperation in region. The model assists to explain pattern, characteristic and meaning of regional disaster governance in South East Asia that associated to neoliberlism institutionalism about institution existence and completed the explanation about international cooperation execution.